Pemanfaatan TIK berbasis video animasi untuk peningkatan kualitas pembelajaran pada guru di lingkungan IGTKI di Banda Aceh - Oktariana, Riza; Fidiawati , Liza; JS, Hanifa; Agustina , Windi (State Islamic University of Mataram, 2024)
The purpose of this community service activity is to provide training and mentoring to educators so that they have the ability to design and design learning media in the form of animated videos with various themes/subthemes/topics so that the quality of learning will improve according to the development aspects of early childhood. This Community Service activity is also related to the IKU of Bina Bangsa University, namely that each lecturer is challenged to develop innovations to improve community welfare in supporting government programs, especially those related to educational innovation. This service is carried out in four stages, namely the preparation, planning, implementation, and evaluation stages. With the implementation of this activity, it can later increase the experience, insight, and skills of teachers in designing and designing learning media in the form of animated videos according to the theme/subtheme/topic for early childhood.